2020
DOI: 10.1007/s11906-020-01101-w
|View full text |Cite
|
Sign up to set email alerts
|

Renin-Angiotensin System Inhibitors and COVID-19: a Systematic Review and Meta-Analysis. Evidence for Significant Geographical Disparities

Abstract: Purpose of Review While the COVID-19 pandemic is constantly evolving, it remains unclear whether the use of angiotensinconverting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) affects the clinical course of SARS-CoV-2 infection. For this meta-analysis, PubMed, CENTRAL, and grey literature were searched from their inception to 19 May 2020 for randomized, controlled trials or observational studies that evaluate the association between the use of either ACE inhibitors or ARBs and the risk for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 57 publications
0
48
1
3
Order By: Relevance
“…Accordingly, one must adjust for indication bias in patients who are on or not on ARBs or ACE inhibitors. Some prior meta-analyses and studies found that use of ARBs and/or ACE inhibitors were not associated with altered mortality (10)(11)(12)(13)(14)(15)(16), while one meta-analysis found that ACE inhibitors but not ARBs were associated with decreased COVID-19 mortality or critical illness (17) and others found that the use of ARBs or ACE inhibitors was associated with decreased mortality overall (18,19) or in patients with cardiovascular disease (20) or hypertension (21)(22)(23)(24)(25). The reason for these conflicting results could partly be due to methodological differences.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, one must adjust for indication bias in patients who are on or not on ARBs or ACE inhibitors. Some prior meta-analyses and studies found that use of ARBs and/or ACE inhibitors were not associated with altered mortality (10)(11)(12)(13)(14)(15)(16), while one meta-analysis found that ACE inhibitors but not ARBs were associated with decreased COVID-19 mortality or critical illness (17) and others found that the use of ARBs or ACE inhibitors was associated with decreased mortality overall (18,19) or in patients with cardiovascular disease (20) or hypertension (21)(22)(23)(24)(25). The reason for these conflicting results could partly be due to methodological differences.…”
Section: Introductionmentioning
confidence: 99%
“…In another meta-analysis where the relationship of the use of RAASBs with the probability of COVID-19 is stated, geographical differences are evidenced, detecting that the use of RAASBs is generally associated with a better prognosis only in studies carried out in Asian countries (OR.0.37; 95% CI: 0.16-0.89) whereas, in those carried out in North America, it is commonly associated with an even more significant increase in ICU admissions (OR: 1.75; 95% CI: 1.37-2.23) and in those carried out in Europe it is related with a higher death probability (OR: 1.68; 95% CI: 1.05-2.70). The authors note that ACEIs would be mainly protective and conversely, ARBs would be associated with an increased risk of death [32]. In a different sense are the findings of the meta-analyses of Megaly et al [33] and Chan et al [34].…”
Section: Discussionmentioning
confidence: 99%
“…While the pandemic is rapidly evolving, the neutral effect of RASi exposure on mortality is increasingly recognized, although some disparities exist. Patoulias et al [ 15 ] showed that, although the use of RASi does not increase the odds for SARS-CoV-2-related death in a global scenario (OR = 1.06, 95% CI 0.77–1.47, I 2 = 83%), it increases the odds for death in Europe by 68% (OR = 1.68, 95% CI 1.05–2.70, I 2 = 82%), while decreasing it in Asia by 38% (OR = 0.62, 95% CI 0.39–0.99, I 2 = 0%). Others have come to the same nonsignificant results in a global perspective, but no subgroup analysis by region was made [ 16 ].…”
Section: Discussionmentioning
confidence: 99%